Obstructive Sleep Apnea in the Formerly Preterm Infant: An Overlooked Diagnosis - Sharma, Preeti B.; Baroody, Fuad; Gozal, David; Lester, Lucille A. (Frontiers in Neurology, 2011)
Background. Obstructive sleep apnea syndrome (OSAS) is a frequent disorder in children. The clinical characteristics of OSAS in very young children under 2 years of age, and more particularly, in those born prematurely, and who have respiratory complications such as bronchopulmonary dysplasia (BPD), are not well defined. We therefore retrospectively reviewed our experience in a group of preterm infants with OSAS. Methods. The records of premature infants with BPD followed in the Pediatric Pulmonary Clinic at the University of Chicago who were diagnosed with OSAS from 2004-2009 were reviewed and analyzed. Results. Twelve children, 8 males and 4 females with a mean gestational age of 27 weeks were found to have OSAS. Mean age at diagnosis was 19 months. Inability to wean nighttime oxygen, the need to resume oxygen after intercurrent respiratory illness, and snoring were the most common presenting symptoms. The apnea-hypopnea index (AHI) ranged from 1 to120/hrTST (mean: 29). SpO2 nadir ranged from 50% to 91%. Despite adenotonsillectomy (T&A), all children had persistent sleep disordered breathing. Conclusions. In preterm infants, while snoring is a frequent symptom, poor weight gain and inability to wean nighttime oxygen may indicate the need for further investigation for OSAS. In the former preterm infant structural changes in the airway may play an important role along with adenotonsillar hypertrophy. A high index of suspicion is required to identify OSA in the formerly preterm infant.